Development and Evaluation of Learning Resource Package in Optics for Grade 10 Science - Recede, Reynald Alfred A.; Gaviola, Robert J.; Castro, Mark A.; Clemente, Shynne Izza F. (Future Science / FSH-PH Publications, 2022)
Learning complicated topics in Physics is one of the most challenging tasks students experi-ence in the classroom. Physics teachers use supplementary materials and laboratory exercises to help students visualize and imagine what they are studying in order to better understand the topics. These learning aids, however, are sometimes not sufficient. Students would still struggle to learn due to lack of effective teaching materials. Without effective teaching materials, it is impossible to master Physics concepts. The study focused on developing and evaluating a learning resource package in Optics for Grade 10 Science. The results showed that the resource package will provide an effective and alternative method for students to be exposed to the scientific method and to explore and observe what the beauty of physics does in our lives. These are very helpful for teachers when teaching Physics concepts. Furthermore, because the learning resource package is already complete, the teacher may feel more prepared to teach optics classes. It is recommended that teacher-writers create lessons that are similar to those already used in science classrooms which may directly address the needs of students.